A starch molecular basis for aging-induced changes in pasting and textural properties of waxy rice. (30th June 2019) - Wu, Peng; Li, Changfeng; Bai, Yeming; Yu, Shiyao; Zhang, Xiaoai
Highlights: Molecular structures and functional properties of fresh and aged rice were characterized. Aging-induced degradation of starch molecular size and chain length of amylopectin. Aging caused higher pasting viscosity and hardness while lower stickiness of cooked rice. Starch molecular degradation caused the changes in textural and pasting properties. Abstract: The gelatinization behavior of rice flour and isolated starch and the texture of cooked rice were examined both for fresh and aged samples successively. The whole and debranched starch molecular structures of the starches extracted from the flour and hot water-washed leachate of the cooked rice were characterized, using size-exclusion chromatography, to elucidate the molecular origins of the functional changes. For all variety, the native and leached starches of the aged rice had significantly smaller average total molecular sizes, higher proportions of short amylopectin chains, and smaller average chain length of amylopectin compared to fresh rice. The structural changes are consistent with the observed higher peak and final viscosity, lower pasting temperature, greater hardness and lower stickiness of cooked rice kernels for aged rice, based on established structure–property relationships. This study can be used to suggest ways in which some improved functional properties could be obtained with less expenditure for storage.